2015
DOI: 10.1089/bari.2014.0053
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Postoperative Aftercare Attrition among Gastric Bypass Patients

Abstract: Background: Poor adherence to post-bariatric surgery aftercare continues to challenge surgical practices. The objective of this study was to identify factors that predict poor aftercare attendance among patients who underwent Roux-en-Y Gastric Bypass (RYGB) surgery. Method: A retrospective medical chart review of patients who underwent RYGB from 2002 to 2011 was conducted. Patients with four visits or more in the first 2 years ( > 50%) were categorized as ''acceptable follow-up'' and with £ 50% as ''poor follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 30 publications
2
34
2
1
Order By: Relevance
“…As for the Ethanol, which also entered the model, showed no association (p>0.05) (Table 4). International surveys indicate progressively low rates of adherence to scheduled appointments in the postoperative period: 50% in the first year, 30% in two years, and <10% in ten years 9,18,19 . In Brazil, despite extensive research, we found no specific studies on the rates of medical-surgical followup, only nutritional.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As for the Ethanol, which also entered the model, showed no association (p>0.05) (Table 4). International surveys indicate progressively low rates of adherence to scheduled appointments in the postoperative period: 50% in the first year, 30% in two years, and <10% in ten years 9,18,19 . In Brazil, despite extensive research, we found no specific studies on the rates of medical-surgical followup, only nutritional.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, laparoscopic Sleeve gastrectomy (LSG) presents lower morbidity, but with complications that may require long-term reoperations. Therefore, regular medical-surgical and multiprofessional follow-up is extremely important to prevent and treat complication soon 9,10 . The Brazilian recommendations for postoperative follow-up emphasize the regularity and importance of maintaining it, to early detect metabolic and nutritional changes, as well as to monitor weight [11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some research indicates that male patients have a particularly difficult time conforming to medicalized ideas about “adherence” following bariatric surgery (Khorgami et al. ; Toussi et al. ).…”
Section: Why Men? Why Bariatric Surgery?mentioning
confidence: 99%
“…One of the most detailed ethnographic studies of post-surgical patients (in Norway) concluded that men still struggled to negotiate their new bodies and the effects of surgery five years afterward (Natvik et al 2015). Some research indicates that male patients have a particularly difficult time conforming to medicalized ideas about "adherence" following bariatric surgery (Khorgami et al 2015;Toussi et al 2009). Other scholarship has investigated the ways in which men's intimate and professional relationships are altered following bariatric surgery (Moore, Brooks, and King 2016;Moore and Cooper 2016).…”
Section: Why Men? Why Bariatric Surgery?mentioning
confidence: 99%